VFPI an isolation device for aseismic design. - Pranesh, M.
Sliding isolators with curved surface are effective base isolation systems incorporating isolation, energy dissipation and restoring mechanism in one unit. However, practical utility of these systems, such as friction pendulum system (FPS) has limitations due to constant isolator period and restoring force characteristics. A new isolator called the variable frequency pendulum isolator (VFPI) that overcomes these limitations while retaining all the advantages has been described in this paper. VFPI has oscillation frequency decreasing with sliding displacement, and the restoring force has an upper bound so that the force transmitted to the structure is limited. The mathematical formulations for the response of a SDOF structure and energy balance are also described. Parametric studies have been carried out to critically examine the behaviour of structures isolated with VFPI, FPS and PF system. From these investigations, it is concluded that the VFPI combines the advantages of both FPS and PF system, without their undesirable properties. The VFPI performance is also found to be stable during low intensity excitations, and fail safe during high intensity excitations. VFPI is found to exhibit robust performance for a wide range of structure, isolator and ground motion characteristics clearly demonstrating its advantages.
Keywords: Structural control; Base isolation; Energy dissipation; Earthquake engineering; Passive control; VFPI